Analisis Pengaruh Kepercayaan Terhadap Loyalitas Pasien Melalui Nilai Pasien di RS Islam Sultan Agung pada Masa Pandemi Covid-19 - Yuzzi Afraniza; Zahroh Shaluhiyah; Septo Pawelas Arso (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
Trust in management and policy practice (MPP) and in front line employee (FLE) at hospital are essential factors that need to be assured in the Covid-19 pandemic so that patients can feel safe. Patients’ trust in this pandemic is mainly influenced by patients’ experiences while using the health service provided by hospital, thus affecting patient’s value that might determine patients’ loyalty. This study is aimed to analyze the effect of trust towards loyalty thorough patients’ value. A quantitative study was conducted by distributing a self-administered questionnaire to outpatients at Sultan Agung Hospital during November – December 2021. The partial least squares structural equation modelling (PLS-SEM) was used to analyze the relationships between trust, value, and loyalty. This study showed that patients’ trust to MPP have positive association towards patients’ value to FLE (H1: t-values = 40.597, p < 0.05). A positive association was also observed in patients’ trust to FLE towards patients’ value (H3: t-values =5.915, p < 0.05) and patients’ value towards patients’ loyalty (H4: t-values =25.914, p < 0.05). There was no significant effect of patients’ trust to MPP towards patients’ value (H2: t-values = 1.444, p = 0,149).